PEMBERDAYAAN KADER DALAM UPAYA PENCEGAHAN MALARIA PADA IBU HAMIL DI PUSKESMAS ARSO KOTA KABUPATEN KEEROM - Muji Lestari; Sri Wahyuni; Eka Setyaning Suci (Health Care : Journal of Community Service, 2024)
The incidence of malaria in pregnant women in Keerom Regency in 2020 was 75 people, in 2021 it was 48 people and in 2022 it rose again to 77 people. Arso Kota Community Health Center is a community health center where the incidence of malaria in first-time pregnant women has been quite high in the last three years, namely 12 people in 2020, then decreased to 10 people in 2021 and increased again in 2022 to 21 people.   The aim of this community service activity is to assist the Community Health Center in reducing malaria rates in pregnant women by empowering cadres. The method used is to empower malaria cadres by providing education about malaria prevention, malaria diagnosis and malaria management using a pocket book. Cadres are also trained to carry out RDT checks.  The results showed that knowledge about malaria among the cadres who were trained increased on average, where the average pre-test score was 70 and the average post-test score was 90. The level of skill in carrying out RDT examinations for cadres increased, where the pre-test skill score was 60 and the post test skills score was 95. Conclusion This activity was successful in increasing the knowledge and skills of malaria cadres in preventing malaria in pregnant women at the Arso City Community Health Center. Continuation of this program is highly recommended to maintain the results achieved.